(2x-9)3=8-3x

Simple and best practice solution for (2x-9)3=8-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-9)3=8-3x equation:


Simplifying
(2x + -9) * 3 = 8 + -3x

Reorder the terms:
(-9 + 2x) * 3 = 8 + -3x

Reorder the terms for easier multiplication:
3(-9 + 2x) = 8 + -3x
(-9 * 3 + 2x * 3) = 8 + -3x
(-27 + 6x) = 8 + -3x

Solving
-27 + 6x = 8 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-27 + 6x + 3x = 8 + -3x + 3x

Combine like terms: 6x + 3x = 9x
-27 + 9x = 8 + -3x + 3x

Combine like terms: -3x + 3x = 0
-27 + 9x = 8 + 0
-27 + 9x = 8

Add '27' to each side of the equation.
-27 + 27 + 9x = 8 + 27

Combine like terms: -27 + 27 = 0
0 + 9x = 8 + 27
9x = 8 + 27

Combine like terms: 8 + 27 = 35
9x = 35

Divide each side by '9'.
x = 3.888888889

Simplifying
x = 3.888888889

See similar equations:

| 8(3x-7)=2(12x+3) | | (x-3)(x+2)=(x-4)(x+1)-(x+1)(x+2) | | 25m=-125 | | -16x+6y=-26 | | 10z-z=-1+7z-2-1 | | 8x+10y=26 | | 7m+3m=30 | | 10x-10y=-20 | | 8(2x-7)=2(12x+3) | | 21x-7=5+19x | | 2x+2=3x+9 | | -2x+6y-3=0 | | 10x-9y=-15 | | (y+3)(y+5)=(y+1)(y+6)+(y+6)(y+5) | | -8x-2y=-20 | | -8x+4=10-5x | | 2.5+1=3d-4 | | -9x+5y=21 | | 10m+7=-7m+-11 | | 11c-10c=18 | | 12(2z+11)=12(2z+12) | | 10(g+3)-(-9g-4)=g-5+3 | | 4(x-2)(x-1)-3(x-2)=3 | | (3x-9)(8x-2)=0 | | 6(x+3)(x-1)-6(x-1)=-5(x+3) | | 15x^2-38x+24=0 | | 7n=-14 | | 4x-10=-4z+22 | | 66-=(x+24)+3(x-28) | | -8(2b+1)+(17b-5)=0 | | 2x^4-16x^3+32x^2=0 | | 9x^2+37x-40=0 |

Equations solver categories